(untitled) (Research, Society and Development, 2022)
The present work aimed to dynamically encourage the teaching-learning process of polymer content for high school. The roulette game “Polymerando a chemistry” on the content of polymers was applied in 3rd grade classes at Escola Estadual Manoel André, municipality of Arapiraca - AL. The action research was developed in 5 phases: 1) survey questionnaire; 2) expository-dialogued class; 3) game construction; 4) game application; 5) reapplication of the survey questionnaire. The application of the roulette game provided the students with a dynamic class, outside the traditional teaching pattern, which they were used to. After the application of the game “Polymerizing chemistry”, 94% of the students were able to identify what polymers would be. Regarding the question of what plastics would be, there was a 56% increase in the number of correct answers by students. In the third question, about the origin of polymers, 78% of the students obtained exact answers. Finally, when dealing with basic knowledge about polymer content, 94% of students demonstrated assimilation of the subject. The positive influence that the ludic activity provided for these groups is clear, the results showed that there was an understanding of the students about the Polymers subject, as well as an improvement in the performance and yield of the activities carried out.